Determination of factors on the volume of violations in a budget institution - Дікань, Лариса Василівна; Дейнеко, Євген Валерійович (Technology audit and production reserves, 2013)
A model of forecasting factors and factors of influence on the number of violations in a budget institution has been developed. It allows not only to determine the importance of each factor, but also to predict their impact. The factors taken for the model are: the volume of institutions’ financing, wages, staff growth, the quantity of workers developed their skills’ level. The scientific impact of this research is the ability to justify methodological approach to determine the effect of factors on the volume of violations in a budget institution, the mechanism of the relationship between factors and effective feature-based development of econometric regression models. However, as the direction of future research the need to adapt this developed econometric model for each of the budget institution is to be ouitlined.